Reproductive performance of yearling beef heifers after estradiol benzoate and estrous synchronization - R.P. Bolze; C.W. Peters (Kansas Agricultural Experiment Station Research Reports, 1993)
Injectable estradiol (estradiol benzoate) was evaluated for its effect on the reproductive performance of yearling beef heifers whose estrous cycles were synchronized using the melengestrol acetate/prostaglandin F 2 Î± (MG- 2 A®/PG) system. Estradiol was injected 40 h after prostaglandin. Heifers were inseminated artificially (AI) 12 h after first observed heat during a 35-d AI period followed by 28 d of bull exposure. Estradiol had no effect on heat response or first-service pregnancy rate to AI during the synchronized period (5 d) and had no significant effect on overall AI pregnancy rate (35 d), cumulative pregnancy rate (63 d), or average calving date. In summary, estradiol benzoate had no effect on the reproductive efficiency of yearling beef heifers whose estrous cycles were synchronized with the MGA/PG system.
Keywords: Cattlemen' s Day; 1993; Kansas Agricultural Experiment Station contribution; no. 93-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 678; Beef; Heifer; Estrous synchronization; MGA; Prostaglandin; Estradiol benzoate